A Cross-sectional Study Relationship Between Coffee Consumption Habits and Farmers' Blood Glucose Levels in Jenggawah Village, Jenggawah Subdistrict, Jember Regency - Sugiyanta Sugiyanta; Muhammad Isra Rafidin Rayyan; Ali Santosa (Universitas Nahdlatul Ulama Surabaya, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder and a major global problem. Coffee contains several bioactive compounds, such as caffeine, chlorogenic acid, trigonelline, cafestol, and kahweol, associated with a reduced risk of type 2 DM. This study aimed to assess the relationship between coffee consumption habits and blood glucose levels of farmers in Jenggawah Village, Jenggawah Subdistrict, Jember Regency. We used a cross-sectional study design. The sample of this study was 137 farmers who were taken by purposive sampling. Assessment of coffee consumption habits was conducted using a questionnaire. At the same time, data on random blood glucose levels were obtained from medical records of the Bakti Sosial Akbar dan Pengobatan Gratis Agromedis activities in Jenggawah Village in June 2022. Statistical analysis was performed using the Kruskall-Wallis test, and multivariate analysis using linear regression. The results showed that there was no statistically significant difference in random blood glucose levels between groups based on the variable type of coffee consumed (p=0.212), the level of coffee consumption (p=0.211), and the amount of sugar added to the coffee (p=0.086). However, the linear regression test results showed that the amount of added sugar in coffee had the greatest relationship with blood glucose levels compared to other independent variables (p=0.031). In conclusion, there was no relationship between coffee consumption habits and random blood glucose levels of farmers in Jenggawah Village. Further research is needed to confirm these findings.